Cultural competence education for health professionals from pre-graduation to licensure delivered using facebook: Twelve-month follow-up on a randomized control trial. (December 2017) - Chang, Li-Chun; Guo, Jong Long; Lin, Hui-Ling
Abstract: Background: Cultural competence (CC) training is widely recognized as a crucial component of the professional development of healthcare providers. There is no study on the effect of Facebook (FB) as a strategy to promote continual learning to enhance CC among students in health professions. Objectives: To test the effects of cultural competence education using FB as a delivery platform on knowledge, awareness, self-efficacy, and skill related to CC in health students from pre-graduation to licensed professional stages. Design: A randomized controlled trial. Participants: We recruited students from professional nursing, pharmacy, and nutrition programs at six medical universities and randomly assigned them to study groups. Methods: Between T1 and T2 (months 1–3), the intervention group (IG) received pre-graduation education in CC while the control group (CG) received their regular educational program. Between T2 and T3 (months 6–9), IG received on-the-job education in CC while CG received the regular program. An online self-report questionnaire assessing CC knowledge, awareness, self-efficacy, and skill was analyzed at baseline, 6 months, and 12 months. Results: Of 180 participants who completed the pretest, 120 (65 IG and 55 CG) completed both follow-ups. Changes over time were mixed; the only statistical difference between groups was an improvement in awareness in IG but not in CG. At 12 months, intervention and control participants had different levels of awareness of CC (β = 2.56, p  < 0.001), but other outcomes did not differ between groups. Conclusion: Health profession educators can adopt Facebook as an education delivery platform to offer personalized, social learning incorporating cultural competency curricula into ongoing education and training in rising awareness on CC. Highlights: Effects of Facebook cultural competence education on health professionals CC education raises CC knowledge, awareness, skill, and self-efficacy. Intervention group saw a statistically greater gain in awareness than CG. No other meaningful differences were seen based on questionnaire results.